2014
DOI: 10.1103/physreva.90.042701
|View full text |Cite
|
Sign up to set email alerts
|

Ionization-excitation of helium by high-resolution(e,2e)spectroscopy and 4-body distorted-wave calculations

Abstract: We present experimental and theoretical results for electron-impact-induced ionization and excitation of helium atoms. Using a high-sensitivity and high-resolution (e, 2e) spectrometer, we measured the differential cross sections of ionization-excitation of He to the n = 1−5 states of He + at an impact energy of 600 eV. The experimental results are compared with 4-body distorted wave (4DW) calculations and first Born approximation (FBA) calculations. It was found that 4DW can well describe the shapes of the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Unfortunately, there is currently only limited experimental data available for out-of-plane excitation-ionization collisions [26], but a comparison of our 4DW calculations to this data shows good shape agreement. We therefore expect that the three-dimensional FDCS presented here are an accurate prediction, and hope that this work prompts further study of the excitation-ionization process.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Unfortunately, there is currently only limited experimental data available for out-of-plane excitation-ionization collisions [26], but a comparison of our 4DW calculations to this data shows good shape agreement. We therefore expect that the three-dimensional FDCS presented here are an accurate prediction, and hope that this work prompts further study of the excitation-ionization process.…”
Section: Discussionmentioning
confidence: 63%
“…In recent years, there has been an increased focus on electron and heavy ion impact single ionization fully differential cross sections (FDCS) in which the ionized electron is found outside of the scattering plane [9][10][11][12][13][14][15][16]. However, almost all of the recent studies of excitation-ionization have focused on FDCS where the ionized electron is found in the scattering plane [17][18][19][20][21][22][23][24][25][26][27]. In single ionization FDCS, unexpected structures were observed outside of the scattering plane in experimental results, particularly for heavy ion projectiles [9].…”
Section: Introductionmentioning
confidence: 99%